An Examination of Long Term Fluctuations in Prices and Wages for North Babylonia during the Old Babylonian Period - Farber, Howard Martin (1974)
A Thesis Submitted to the Graduate School in Partial Fulfilment of the Requirements for the Degree of Master of Arts; Thesis director, Marvin A. Powell, Jr.